Cervical spine injury response to direct rear head impact. (February 2022) - Beauséjour, Marie-Hélène; Petit, Yvan; Wagnac, Éric; Melot, Anthony; Troude, Lucas; Arnoux, Pierre-Jean
Abstract: Background: Direct rear head impact can occur during falls, road accidents, or sports accidents. They induce anterior shear, flexion and compression loads suspected to cause flexion-distraction injuries at the cervical spine. However, post-mortem human subject experiments mostly focus on sled impacts and not direct head impacts. Methods: Six male cadavers were subjected to a direct rear head impact of 3.5 to 5.5 m/s with a 40 kg impactor. The subjects were equipped with accelerometers at the forehead, mouth and sternum. High-speed cameras and stereography were used to track head displacements. Head range of motion in flexion-extension was measured before and after impact for four cadavers. The injuries were assessed from CT scan images and dissection. Findings: Maximum head rotation was between 43 degrees and 78 degrees, maximum cranial-caudal displacement between −12 mm and − 196 mm, and antero-posterior displacement between 90 mm and 139 mm during the impact. Four subjects had flexion-distraction injuries. Anterior vertebral osteophyte identification showed that fractures occurred at adjacent levels of osteophytic bridges. The other two subjects had no anterior osteophytes and suffered from C2 fracture, and one subject also had a C1-C2 subluxation. C6-C7 was the most frequently injured spinal level. Interpretation: Anterior vertebral osteophytes appear to influence the type and position of injuries. Osteophytes would seem to provide stability in flexion for the osteoarthritic cervical spine, but to also lead to stress concentration in levels adjacent to the osteophytes. Clinical management of patients presenting with osteophytes fracture should include neck immobilization and careful follow-up to ensure bone healing. Highlights: A novel protocol was created to apply dynamic rear head impact on human cadavers. Neck anterior shear and compression loading leads to flexion-distraction injuries. Anterior vertebral osteophytes provide stability in flexion to the cervical spine. Osteophytes seem to influence the type and location of injuries at the cervical spine.